Forest users' level of participation in a participatory forest management program in southwestern Ethiopia. Issue 4 (2nd October 2017) - Tadesse, Solomon; Woldetsadik, Muluneh; Senbeta, Feyera
ABSTRACT: This study examines the level of forest users' participation at different stages of a participatory forest management (PFM) program, and identifies factors that influence their level of participation in the Gebradima forest, southwest Ethiopia. Data were collected from five forest user groups (FUGs) through household surveys, key informant interviews, and focus group discussions. A participation index (PI) and binary logistic regression model were used to analyze the data. Results revealed that the level of the forest users' PI was 65.7%, 59%, and 54.9% at the planning, implementation, and monitoring stages, respectively. The logistic regression model showed that gender, family size, education level, income from the forest, distance of the forest from home, restriction on charcoal and timber harvesting, elite domination in decision-making processes, and lack of incentives were found to be statistically significant ( P < 0.05) predictors for the level of participation. Thus, this study suggests that policy-makers and project designers should consider these factors in making future PFM implementation strategies to improve the level of forest users' participation in forest management activities.